Cost of Production to Determine Selling Price in Gowa Jaya Cake - Dangkeng, Arianto; Ramli, Muh.; Nurfaisah, Nurfaisah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the selling price of the product using a full costing approach at Gowa Jaya Cake. The type of research used in this research is case study research with qualitative methods. The data used in this study are primary data and secondary data. Processed data is data in the form of records of the cost of production such as raw material costs, labor costs, and factory overhead costs. While the data analysis technique used in this research is the full costing method. The results of the study indicate that the costs incurred in the production of Gowa Jaya Cake bread have a major influence in determining the selling price of the bread itself, such as calculating the cost of production using the full costing method.